Characteristics and response to treatment among Indigenous people receiving injectable diacetylmorphine or hydromorphone in a randomised controlled trial for the treatment of long‐term opioid dependence. (8th June 2017) - Oviedo‐Joekes, Eugenia; Palis, Heather; Guh, Daphne; Marchand, Kirsten; Brissette, Suzanne; Lock, Kurt; MacDonald, Scott; Harrison, Scott; Anis, Aslam H.; Krausz, Michael; Marsh, David C.; Schechter, Martin T.
Abstract: Introduction and Aims: To determine the effectiveness of injectable hydromorphone and dicaetylmorphine for Indigenous participants in the Study to Assess Longer‐term Opioid Medication Effectiveness (SALOME) clinical trial. The study additionally aims to explore the prevalence and frequency of crack cocaine use among subgroups of participants (by gender and ethnicity). This secondary analysis is particularly relevant given the current need for expanded medication assisted treatments for opioid dependence across North America. Design and Methods: Participants self‐identifying as First Nations, Métis or Inuit were included in the analysis of Indigenous participants. Six‐month treatment outcomes are reported as the difference between diacetylmorphine and hydromorphone treatment arms among Indigenous participants and change from baseline to 6 months in each treatment arm. Differences in outcomes are tested between Indigenous and non‐Indigenous participants. Crack cocaine use was explored to determine differences between and within subgroups. Results: Approximately one‐third of SALOME participants self‐identified as Indigenous. Indigenous participants presented to treatment with more structural vulnerabilities (e.g. lower education, higher rates of foster care and separation from biological parents) compared to non‐Indigenous participants. After 6 months, Indigenous participants in both treatment arms had a significant reduction in days of street heroin use, opioid use, crack cocaine use and illegal activity. Treatment retention did not differ by treatment arm. Discussion and Conclusions: Indigenous people that are not engaged by first‐line treatments for opioid dependence are in need of effective alternative treatments. Given the political and logistical barriers facing diacetylmorphine, hydromorphone could serve as a more accessible medication to reach and treat this population. [Oviedo‐Joekes E, Palis H, Guh D, Marchand K, Brissette S, Lock K, MacDonald S, Harrison S, Anis AH, Krausz M, March DC, Schechter MT. Characteristics and response to treatment among Indigenous people receiving injectable diacetylmorphine or hydromorphone in a randomised controlled trial for the treatment of long‐termopioid dependence. Drug Alcohol Rev 2018;37:137–146]